EFEKTIFITAS PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) DALAM MENUMBUHKAN PERILAKU KOOPERATIF - Faizah, Kurniyatul (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2018)
Learning activities at this time have begun to shift in learning activities that are oriented to character development (character building) in which previous learning focused on individualistic individual development, namely learning that leads to competition for achievement among students. Learning that is oriented towards the cognitive achievement of students will generally shape the character of individual students, each student will be obsessed to be number 1 from other friends. The values ??of cooperation are not directly ignored in the learning process. The application of the Group Investigation (GI) learning model is one alternative model of learning that is effective in instilling the values ??of cooperation in conducting learning activities with the aim of familiarizing students to be able to work well together with others in each activity as well as fostering sensitivity of students to responsive provide assistance to people in need. Group Investigation (GI) learning model is one of Cooperative learning that is carried out in groups or individuals (Endang Mulyatinningsih, 2013: 234). This investigation group model provides the widest opportunity for students to be directly and actively involved in the learning process from planning to how to learn a topic through investigation. The application of the GI model is based on a combination of several rationale, which is based on constructivist views, democratic teaching, and cooperative learning groups. Based on constructivist views, the learning process with the investigation group model provides the widest opportunity for students to be directly and actively involved in the learning process from planning to how to learn a topic through investigation. Democratic teaching is a learning process based on democratic values, namely respect for ability, uphold justice, apply equality of opportunity, and pay attention to the diversity of students (Budimansyah, 2007: 7). Based on this rationale, the application of the Group Investigation (GI) learning model is believed to be effective in fostering the values ??of cooperation in each student's activities.